Heterogenization of [Ru(bpy)3]Cl2 on Ordered Mesoporous Silica Materials for Photocatalytic Applications - Sebbat, Malik; Lazar, Anish; Laurent, Claire; Despas, Christelle; Vilà, Neus; Walcarius, Alain; McClenaghan, Nathan; Oheix, Emmanuel; Lebeau, Bénédicte; Cormier, Morgan; Goddard, Jean-Philippe (Synlett, 2024)
Herein, the preparation and characterization of three Ru-based heterogeneous photocatalysts supported on ordered mesoporous silica materials are reported. The photocatalytic activity of these catalysts was evaluated through oxidation, reduction, cycloaddition, and carboxylation reactions and their efficiencies are comparable to the parent [Ru(bpy)3]Cl2 under homogeneous conditions. These photocatalysts are efficiently recovered even after five reaction cycles offering new opportunities in sustainable chemistry.
Keywords: heterogeneous photocatalysis; ordered mesoporous silica; [Ru(bpy)3]Cl2; sustainable chemistry